Upaya Teknis Rehabilitasi TPA Sampah Kopi Luhur dengan Sistem Lahan Urug Terkendali - Isni, Nendia Nur; Sungkowo, Andi; Widiarti, Ika Wahyuning (Jurnal Ilmiah Lingkungan Kebumian, 2020)
The risk index value of Kopi Luhur Waste Landfill is 575.3536, classified as moderate hazard category and the suggested action is to continue the landfill and apply the rehabilitation into a controlled landfill system gradually. The purpose of this research are to de design the rehabilitation steps based on some measurement in Kopi Luhur Waste Landfill. The purpose of this research are to design the process of landfill mining in unactive landfill and to design a landfill with controlled landfill system. The methodology in the research are survey & mapping method and measurement of waste composition. The landfill mining process and the controlled landfill system is designed based on The Minister of Public Works Regulation No.3/2013 and the existing condition of Kopi Luhur Waste Landfill. The result shows that Kopi Luhur Waste Landfill consists of 9.09% hazardous waste, 12.91% biodegradable waste and 58% non-biodegradable waste. The waste composition become a reference in conducting landfill mining and the rehabilitation process of Kopi Luhur Landfill into controlled landfill is applied after applying the landfill mining process. The new landfill land area with a controlled landfill system has a length of 198 m and a width of 65, which has 3 layers with a thickness of 5 m. The waste is spread into a thickness of 0.5 m, compressed by heavy equipment and then covered by a 20 cm daily overburden when the waste lift reaches 2.5 m. In addition, the landfill system is equipped with environmental protection facilities such as the base layer, drainage system, leachate collection network and gas control system. The implementation of the controlled landfill system make the new landfill has 6.6 years lifespan. Keywords: Kopi Luhur Waste Landfill, Controlled Landfill, Landfill Mining